Voting Radical Right in Europe: a Comprehensive Explanation for Vote Choice - (:unkn) unknown (My University, 2016)
Although the radical right in liberal democracies have received a wealth of attention in the literature, the mechanisms explaining individual radical right vote choice are unclear. This analysis provides the first comprehensive theoretical framework and empirical modeling of individual radical right vote choice. The choice to vote for a radical right party is a function of several factors. First, the opportunity structure in the form of external supply-side factors must be conducive for radical right success. Second, parties must make crucial decisions in order to take advantage of the opportunity structure (internal supply-side factors). Then, macro-social force illicit the adoption of crucial attitudes correlated with the radical right. Finally, these attitudes directly impact vote choice for radical right parties. This dissertation finds that attitudes alone do not necessarily lead to voting for a radical right party. Instead, macro-forces and supply-side factors play a significant role in the ability and desire to cast a vote for radical parties.
Keywords: Electoral Studies; European Politics; Political Parties; Radical Right Parties; Voting Behavior